P1.021 A National Study Utilising the Sequenom Massarray iPLEX Platform For High Throughput MLST-Based Typing and Characterisation of Resistance Mechanisms in Neisseria Gonorrhoeae. (13th July 2013) - Trembizki, E; Chen, M; Donovan, B; Fairley, C; Guy, R J; Kaldor, J M; Lahra, M M; Regan, D G; Ward, J; Whiley, D
Abstract : Introduction: Strain-typing and characterisation of associated resistance mechanisms is pivotal to understanding the development and spread of Neisseria gonorhoeae (NG) antimicrobial resistance (AMR). In Australia, we have embarked on a national study to determine the molecular basis of AMR in our local isolates with a view to implementing broad-based molecular surveillance for NG AMR. Methods: In this initial phase of the study, called GRAND (Gonorrhoea Resistance Assessment via Nucleic acid Detection), we are using the Sequenom MassARRAY iPLEX MALDI-TOF MS platform to characterise all available isolates (n = 2373) collected throughout Australia in the first half of 2012. To date, two iPLEX methods have been developed and validated: (1) a typing method targeting 14 informative SNPs previously shown to predict an MLST type; and (2) an AMR method targeting 11 common mutations associated with N. gonorrhoeae resistance to penicillin, ciprofloxacin, azithromycin and ceftriaxone, including important mutations on the penicillin binding protein (PBP2): A501 substitutions and the mosaic PBP2 sequence. Results: The results to date show that the technology is well suited for high-throughput typing of N. gonorhoeae isolates. In particular, we found it can be used on heat-denatured isolates (removing the need for a commercial DNA extraction kit) and can genotype (using both iPLEX reactions) up to 384 isolates within one working day for less than $AUS20.00 (€15.00) per isolate. Conclusions: The data from this study will provide pivotal information to inform the implementation of molecular-based NG AMR surveillance. Validation and testing is ongoing.